SPEECH DEVELOPMENT IN CHILDHOOD - Tojiddinova Laylokhan Shokirovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
in early childhood, development proceeds in a unique way with self-awareness. Awareness of the motives of his activities. Kureishi to emotional communication is the main type of communication at this age.